Sign systems and authorship styles in indonesian popular poetry - WulandariSovia; WilyantiLiza Septa; TriandanaAnggi (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
The sign system found in poetry is a symbolic sign. These symbolic signs give rise to an authorship style. Therefore, the purpose of this research is to describe the symbolic sign system and classify the style of authorship in Indonesian popular poetry based on the use of the symbolic sign system. The method used in this research is descriptive qualitative using the approach of stylistic criticism and semiotics. The stylistic criticism approach is to describe the authorship style of Indonesian popular poetry writers and the semiotic criticism approach is used to analyze the symbolic sign system in the poems. The results show that the symbolic sign system contained in Indonesian popular poems is symbols in the form of phonemes, words, sentences, and typography. Based on these symbols, it is concluded that there are four styles of authorship, namely: 1) style that relies on phonemes; 2) style that relies on words; 3) style that relies on sentences; and 4) style that relies on typography.